Penentuan Suhu Kalsinasi Optimum CaO dari Cangkang Telur Bebek dan Cangkang Telur Burung Puyuh - Nya Daniaty Malau; Fajar Adinugraha (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2020)
The need for implants increases with the high number of fracture sufferers resulting from accidents both on the road and workplace accidents. Bioceramics is a ceramic product or component used in the medical and dental industry, especially as an implant or organ replacement. Hydroxyapatite is one type of bioceramics that is widely used because it has osteoconductive properties (can stimulate bone growth), bioactive and biocompatible. This study aims to find the optimal temperature of the calcination process of duck egg shells and quails as the basic ingredients of HAp. The research method is calcination of duck eggshells then the optimum temperature produces the best CaO. The calcination results obtained that the optimum temperature of calcination of duck eggshells and quail eggs was 1000oC for 6 hours. The results obtained are CaO with clean white color powder and fine grain size. Keywords : Quail eggshell, calcination, dugg egg shell